Intimacy and distance : conflicting cultures in nineteenth-century France - Lewis, Philippa (Legenda, an imprint of the Modern Humanities Research Association, 2017)
What do we mean when we talk about intimacy? And when did we begin to talk about intimacy? Rather than approach the concept as an age-old aspect of love, friendship or desire, Intimacy and Distance identifies the nineteenth century as a period in which intimacy and its lexicon came sharply to the fore. Drawing on a diverse range of literary and non-literary sources, Lewis makes a case for thinking historically about intimacy, and recognising its centrality to nineteenth-century reading and writing practices. The book brings together both canonical and neglected writers, from Baudelaire, Flaubert, and Barbey d'Aurevilly to Sainte-Beuve, Eugène Fromentin, and Eugénie de Guérin. Looking beyond boundaries of genre, it analyses verse and prose poetry, diaries and narrative fiction, and arts journalism and travel writing. Lewis demonstrates not only the impact of the idea of intimacy on nineteenth-century French culture, but also the complex aesthetic and ideological conflicts it could incite. --